ANALISIS KONSENTRASI PM10 dan PM2.5 PADA TITIK PEMANTAUAN BUNDARAN HI JAKARTA PUSAT PERI- ODE DATA FEBRUARI-OKTOBER 2021 - A. Rafi Perdana; Atira Indiani Pangastuti; Yosafat Donni Haryanto (Jurnal Samudra Geografi, 2023)
DKI Jakarta Province is the capital city of Indonesia which has five major cities, namely Central Jakarta, North Jakarta, South Jakarta, East Jakarta and West Jakarta with a population density of 15,978 people/km2 in 2021. This province also contributes to gas emissions which cause a decrease in air quality through population, industry and transportation activities. This study took samples of PM2.5 and PM10 concentrations at the Hotel Indo- nesia Roundabout Monitoring Points in February-October 2021. The data used was AQMS (Air Quality Monitoring System) data using the average method which then obtained PM2.5 and PM10 data for analyzed further. The results of the analysis showed that there was a pattern of distribution of daily and monthly PM2.5 and PM10 concentrations. The highest daily distribution pattern occurs on Sunday for PM2.5 and Friday for PM10, while the lowest is on Tuesday. The highest monthly distribution pattern occurred in July and the lowest in February. In PM2.5 most of the concen- trations exceed the maximum limit while PM10 overall the concentration is below the maximum limit in ambient air allowed by the government. The air quality in the HI Roundabout area, when viewed from the concentration of PM2.5, is included in the unhealthy category, while judging from the concentration of PM10, it is included in the moderate category.